Fatigue-resistant rubber and method for producing the same
Patent Information
- Application Number
- CN202611183435.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-16
AI Technical Summary
例如,专利CN122302452A公开了一种通过二维填料石墨与含氟硅烷改性碳纳米管复配增强氟橡胶的方法,降低了裂纹扩展速率,但氟橡胶基体本身弹性较差
本发明实施例提供的耐疲劳橡胶,通过添加白炭黑、改性碳纳米管和有机蒙脱土,在橡胶中形成多尺度补强网络,三者相互穿插、协同作用,形成物理交联结构。在橡胶的使用过程中,该结构能够有效偏转、钝化或终止微裂纹的扩展,减缓裂纹的生长速率,进而提高橡胶的耐疲劳性。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of rubber, and more specifically, to a fatigue-resistant rubber and its preparation method. Background Technology
[0002] Fluorosilicone rubber combines the high and low temperature resistance of silicone rubber with the oil and chemical resistance of fluororubber, making it irreplaceable in harsh environments such as aerospace seals, automotive engine check valves, and petrochemical vibration damping components. However, existing fluorosilicone rubbers generally suffer from early crack initiation, rapid crack propagation, and short fatigue life under long-term repeated tensile and compressive dynamic alternating loads, severely limiting their application in high-end dynamic sealing and high-frequency vibration damping.
[0003] Currently, methods to improve the fatigue resistance of rubber include: filler functional modification, vulcanization system optimization, and nanofiller reinforcement. For example, patent CN122302452A discloses a method for reinforcing fluororubber by compounding two-dimensional filler graphite with fluorinated silane-modified carbon nanotubes, which reduces the crack propagation rate, but the fluororubber matrix itself has poor elasticity. Patent CN122080647A discloses a strong fluorosilicone rubber, which enhances the fatigue resistance of fluorosilicone rubber by composite anti-fatigue agents, achieving a synergistic improvement in high elasticity and fatigue resistance, but the filler dispersion and orientation still need to be improved. Summary of the Invention
[0004] The purpose of this invention is to provide a fatigue-resistant rubber by adding silica, modified carbon nanotubes and organomontmorillonite to form a multi-scale reinforcing network in the rubber. The three components interpenetrate and work synergistically to form a physical cross-linked structure.
[0005] Another objective of this invention is to provide a method for preparing fatigue-resistant rubber by introducing a strong magnetic field environment of 2-3T, utilizing the anisotropy of modified carbon nanotubes to induce them to align in a specific direction along the magnetic field, thereby improving the fatigue resistance of the rubber.
[0006] The technical problem solved by this invention is achieved by the following technical solution.
[0007] On one hand, embodiments of the present invention provide a fatigue-resistant rubber, comprising the following raw materials by weight: 100-110 parts of fluorosilicone raw rubber, 2-8 parts of anti-fatigue agent, 10-20 parts of silica, 0.3-1.5 parts of modified carbon nanotubes, 8-20 parts of organomontmorillonite, 0.5-4.5 parts of crosslinking agent, 0.5-3 parts of dispersant, and 1.5-12 parts of heat-resistant additive.
[0008] In some embodiments of the present invention, the method for preparing the modified carbon nanotubes includes the following steps: Carbon nanotubes were added to a hydrogen peroxide solution, ultrasonically dispersed for 20-30 min, refluxed at a constant temperature for 4-5 h, and then separated into solid and liquid components. After washing, hydroxylated carbon nanotubes were obtained. Hydroxylated carbon nanotubes were dispersed in an aqueous ethanol solution, and then perfluorodecyltrimethoxysilane was added to adjust the pH to 4-5. The mixture was stirred for 12-18 hours, centrifuged, washed, and dried to obtain modified carbon nanotubes.
[0009] In some embodiments of the present invention, the ratio of carbon nanotubes to hydrogen peroxide is 1 g: (80-100) mL; the amount of perfluorodecyltrimethoxysilane added is 20-40% of the mass of carbon nanotubes.
[0010] In some embodiments of the present invention, the method for preparing the organomontmorillonite includes the following steps: Add intercalating agent solvent to sodium montmorillonite suspension and stir at 70-80℃ for 4-6 hours; centrifuge, wash, dry, grind and sieve the reaction solution to obtain organomontmorillonite.
[0011] In some embodiments of the present invention, the intercalation solvent is a mixture of perfluorooctyltrimethylammonium chloride and diallyldimethylammonium chloride in a mass ratio of 3:1 to 4:1; the mass added is 10-15% of the mass of montmorillonite.
[0012] In some embodiments of the present invention, the crosslinking agent is 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane; the dispersant is trifluoropropyltrimethoxysilane; and the heat-resistant additive is a mixture of cerium oxide and cerium hydroxide in a mass ratio of 1:1.
[0013] On the other hand, embodiments of the present invention provide a method for preparing fatigue-resistant rubber, comprising the following steps: S1, plasticizing raw fluorosilicone rubber to obtain plasticized rubber; S2, put the plasticized rubber into a mixer, then add fatigue-resistant agent, dispersant and heat-resistant additive, and mix for 3-5 minutes; then add fumed silica in batches and mix for 3-5 minutes; then add organomontmorillonite and mix for 3-5 minutes; then add modified carbon nanotubes and mix for 3-5 minutes; discharge the material and sheet it in a two-roll mill to obtain the compounded rubber. S3, add the compounded rubber to the kneader, treat with constant temperature and constant vacuum for 1-1.5 hours, cool, and discharge; S4: Put the rubber compound treated with S3 into a two-roll mill and roll it 3 times. Then add the crosslinking agent and roll it 6-8 times. Then sheet it out and age it at room temperature for 24 hours. S5 undergoes a first vulcanization treatment in a magnetic field, followed by a second vulcanization treatment in a hot air circulating oven, and then natural cooling to obtain fatigue-resistant rubber.
[0014] In some embodiments of the present invention, step S5 includes a primary vulcanization process comprising: Vulcanization treatment for 5-7 minutes at 150-160℃, 5-6MPa, and magnetic field strength of 2-3T. Then, vulcanize for 10-12 minutes at 170-175℃, 10-12MPa, and a magnetic field strength of 2-3T. Then, vulcanize at 180-185℃ and 5-6MPa for 5-6 minutes.
[0015] In some embodiments of the present invention, in step S5, the secondary vulcanization includes: The temperature was increased from room temperature to 120°C at a heating rate of ≤5°C / min, and held at that temperature for 30 min. Heating from 120℃ to 180℃ at a heating rate of ≤3℃ / min, and holding at that temperature for 1-2 hours; Natural cooling.
[0016] In some embodiments of the present invention, in step S3, the temperature of the kneading process in the kneader is 100-110°C and the vacuum degree is -0.095 to -0.098 MPa.
[0017] Compared with the prior art, the embodiments of the present invention have at least the following advantages or beneficial effects: The fatigue-resistant rubber provided in this invention forms a multi-scale reinforcing network within the rubber by adding silica, modified carbon nanotubes, and organomontmorillonite. These three components interpenetrate and synergistically interact to form a physically cross-linked structure. During the use of the rubber, this structure can effectively deflect, passivate, or terminate the propagation of microcracks, slowing down the crack growth rate and thus improving the fatigue resistance of the rubber.
[0018] A strong magnetic field of 2-3T is introduced in the initial stage of vulcanization. Utilizing the anisotropy of modified carbon nanotubes, they are induced to align in a specific direction along the magnetic field. This oriented structure enables the rubber product to achieve higher dynamic modulus and tear resistance in a specific stress direction. Simultaneously, combined with segmented variable pressure vulcanization (5MPa, 12MPa, 5MPa), the optimal pressure is dynamically matched at different crosslinking densities. This ensures the smooth discharge of low-molecular-weight volatiles in the early stages of vulcanization while guaranteeing the dense shaping of the product in the later stages, effectively eliminating internal porosity and flow marks. Detailed Implementation
[0019] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0020] It should be noted that, unless otherwise specified, the embodiments and features described in the present invention can be combined with each other. The present invention will now be described in detail with reference to specific embodiments.
[0021] The features and performance of the present invention will be further described in detail below with reference to embodiments. Example 1
[0022] 1. Prepare modified carbon nanotubes according to the following steps: Step 1: Hydroxylation treatment of carbon nanotubes 10.0 g of carbon nanotubes were added to 1000 mL of a 30% hydrogen peroxide solution. The mixture was placed in an ultrasonic cleaner and ultrasonically dispersed for 25 min at a frequency of 40 kHz and a power of 200 W to ensure complete suspension of the carbon nanotubes. The ultrasonically dispersed suspension was transferred to a round-bottom flask equipped with a reflux condenser and heated in an oil bath to a constant temperature of 85 ± 2 °C for 4.5 h under reflux. After the reaction was completed, the mixture was allowed to cool naturally to room temperature and then separated into solid and liquid components using a high-speed centrifuge (8000 rpm, 15 min). The supernatant was discarded. The resulting precipitate was washed repeatedly with deionized water by centrifugation 3-5 times until the pH of the washing solution was neutral (pH = 6.5-7.0). The washed product was placed in a vacuum drying oven and dried at 60 °C for 12 h to obtain hydroxylated carbon nanotubes (surface hydroxyl content approximately 2.5-3.5 mmol / g).
[0023] Step 2: Grafting modification with perfluorodecyltrimethoxysilane Take 8.0 g of the above-mentioned hydroxylated carbon nanotubes and disperse them in 200 mL of ethanol / water mixed solvent (ethanol to water volume ratio of 9:1). Stir at 300 rpm for 15 min using a magnetic stirrer to form a uniform suspension. Slowly add 2.4 g of perfluorodecyltrimethoxysilane (30% of the carbon nanotube mass) dropwise to the suspension. After the addition is complete, slowly adjust the pH of the system to 4.5 using a 5% glacial acetic acid solution (monitored using a precision pH meter). Raise the system temperature to 40 °C and stir at 400 rpm for 15 h. After the reaction is complete, centrifuge the product (10000 rpm, 20 min), wash twice with anhydrous ethanol and three times with deionized water to thoroughly remove unreacted silane coupling agent and byproducts. Finally, place the product in a vacuum drying oven and dry at 70 °C for 10 h to constant weight. Grind the product through a 200-mesh sieve to obtain the modified carbon nanotubes.
[0024] 2. Prepare organomontmorillonite using the following steps: (1) Raw material preparation: Sodium-based montmorillonite: cation exchange capacity (CEC) of 100 mmol / 100g, particle size ≤74μm (200 mesh), purity ≥98%.
[0025] Intercalating agent A: perfluorooctyltrimethylammonium chloride (C11H13ClF17N, cationic surfactant, purity ≥98%).
[0026] Intercalating agent B: diallyl dimethyl ammonium chloride (C8H16ClN·H2O, aqueous solution with a purity ≥65%).
[0027] Step 1: Pre-swelling treatment of sodium-based montmorillonite Weigh 50.0 g of sodium montmorillonite powder and slowly add it to 1000 mL of deionized water. Stir and disperse the powder at room temperature (500 rpm) for 2 h, and then let it stand to swell for 24 h to obtain a uniform sodium montmorillonite suspension with a mass fraction of about 5%.
[0028] Step 2: Compounding and Adding Intercalating Agents Weigh out intercalating agent A (perfluorooctyltrimethylammonium chloride) and intercalating agent B (diallyldimethylammonium chloride) separately, making their mass ratio 3.5:1. Mix the two intercalating agents and dissolve them in 100 mL of deionized water. Heat and stir in a 50°C water bath until completely dissolved to obtain a compound intercalating agent solution. The total mass of intercalating agent added is 12.5% of the mass of sodium montmorillonite.
[0029] Step 3: Ion exchange intercalation reaction The compound intercalating agent solution was slowly added dropwise to the sodium montmorillonite suspension in step one under stirring, with the addition rate controlled at 3 mL / min. After the addition was complete, the mixture was heated to 75±2℃ and reacted at a constant temperature for 5 hours under mechanical stirring (600 rpm).
[0030] Step 4: Post-treatment and drying After the reaction was complete, heating and stirring were stopped, and the reaction solution was allowed to cool naturally to room temperature. Solid-liquid separation was performed using a high-speed centrifuge (6000 rpm, 15 min), and the supernatant was discarded. The lower precipitate was redispersed with deionized water and washed by centrifugation, repeating this process 5-6 times until no chloride ions were detected in the washing liquid using 0.1 mol / L silver nitrate solution, indicating that the excess intercalating agent had been completely removed. The washed product was placed in a forced-air drying oven and dried at 80°C for 24 h. The dried lumps were ground in a mortar and sieved to obtain the organomontmorillonite.
[0031] 3. Prepare fatigue-resistant rubber according to the following steps and formula. Formula: 105 parts fluorosilicone raw rubber, 5 parts anti-fatigue agent, 15 parts fumed silica, 0.9 parts modified carbon nanotubes, 14 parts organomontmorillonite, 2.5 parts crosslinking agent, 1.5 parts dispersant, and 6.5 parts heat-resistant additive.
[0032] Among them, the fluorosilicone raw rubber comes from Shandong Dongyue Organosilicon Materials Co., Ltd.; The anti-fatigue agent is: hydroxyallyl-butyltrifluoropropylsiloxane; The crosslinking agent is 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane; The dispersant is trifluoropropyltrimethoxysilane; The heat-resistant additive is a mixture of cerium oxide and cerium hydroxide in a mass ratio of 1:1.
[0033] Preparation steps: Step S1: Plasticizing treatment of fluorosilicone raw rubber 1050g of fluorosilicone raw rubber was put into an open mixing mill (open mill) and plasticized in a thin pass under the conditions of 3mm roll gap and 50±5℃ roll temperature. During the plasticizing process, the rubber compound was repeatedly rolled and poured 10 times to reduce the Mooney viscosity [ML(1+4), 100℃] of the raw rubber to the range of 55-65, and the plasticized rubber was discharged and left to stand for 4 hours for later use. Step S2: Segmented mixing in an internal mixer Put all the plasticized rubber obtained in step S1 into a laboratory mixer (effective volume of the mixer chamber is 2.0L, initial temperature is 40℃), and operate according to the following procedure: Adding auxiliary masterbatch: Add 50g of fatigue-resistant agent, 15g of dispersant (trifluoropropyltrimethoxysilane), and 65g of heat-resistant additive (a 1:1 mixture of cerium oxide and cerium hydroxide) to the internal mixer. Mix for 3 minutes at a rotor speed of 60 rpm to ensure that the auxiliary agents are evenly coated on the surface of the raw rubber molecular chains.
[0034] Add silica in batches: Divide 150g of silica into 3 equal batches (50g each), adding one batch approximately every 1.5 minutes. Maintain a speed of 70 rpm and continue mixing for 4 minutes (starting from the first batch) to ensure the silica is fully dispersed and undergoes a preliminary in-situ reaction with the silane coupling agent.
[0035] Add organic montmorillonite: Add 140g of homemade organic montmorillonite into a mixer at once and mix for 3 minutes at 65 rpm.
[0036] Add modified carbon nanotubes: Slowly add 9g of homemade modified carbon nanotubes into the internal mixer (avoid dust) and mix at 60rpm for 3min.
[0037] The total mixing time should be controlled within 13-15 minutes. During this period, cooling water should be circulated through the internal mixer to control the discharge temperature to not exceed 120℃.
[0038] Discharge and Sheeting: The uniformly mixed rubber compound is discharged from the internal mixer and immediately transferred to the open mill (roll gap 1.5mm, roll temperature 40-50℃). It is passed through the mill twice and sheeted to obtain the mixed rubber sheet, which is then naturally cooled to room temperature.
[0039] Step S3: Constant temperature vacuum degassing treatment in a kneader All the mixed rubber sheets obtained in step S2 are put into the vacuum kneader.
[0040] Set the kneader jacket heating temperature to 105℃ (strictly control it within the range of 100-110℃).
[0041] Start the kneader and stir (40 rpm), and at the same time turn on the vacuum pump to draw the vacuum to -0.096 MPa.
[0042] Under constant temperature of 105℃ and constant vacuum conditions, continuous defoaming treatment was carried out for 1 hour.
[0043] After processing, the vacuum and heating are turned off, and cooling water is used to lower the temperature of the rubber compound to below 60°C. The material is then discharged to obtain the defoamed rubber compound.
[0044] Step S4: Re-milling on the open mill and addition of crosslinking agent Re-mixing: Put the rubber compound from step S3 into a two-roll mill (roll gap 2mm, roll temperature 40℃) and mix it 3 times (each time, cut the left and right sides 3 times and roll it, and pass it through the roll gap 1mm once).
[0045] Add crosslinking agent: Evenly sprinkle 25g of crosslinking agent (2,5-dimethyl-2,5-di(tert-butylperoxy)hexane) into the rubber compound on the open mill, and mix at a roller gap of 3mm. After the crosslinking agent is completely absorbed into the rubber compound, continue to mix 6 times (8 times in total) to ensure that the crosslinking agent is microscopically and uniformly distributed in the rubber compound.
[0046] Sheeting and aging: Sheet the final compound rubber on a two-roll mill (about 6-8 mm thick), lay it flat on a stainless steel tray, cover it with polyethylene film to prevent dust, and let it stand and age for 24 hours at room temperature (23±2℃).
[0047] Step S5: Magnetic field-assisted segmented primary vulcanization and hot air secondary vulcanization Magnetic field-assisted primary vulcanization (flat vulcanizing machine and electromagnetic field module): The aged film is cut into standard test pieces, placed into a mold, and then placed in a flat vulcanizing machine equipped with an adjustable magnetic field generator. Vulcanization is then performed according to a three-stage procedure. First stage: Heat to 155℃, apply pressure of 5.5 MPa, turn on the magnetic field generator to make the magnetic field strength at the mold cavity reach 2.5 T, and hold pressure for 6 minutes for vulcanization.
[0048] Second stage: Maintain the magnetic field strength of 2.5T, raise the vulcanization temperature to 172℃, raise the pressure to 11 MPa, and hold the pressure for vulcanization for 11 min.
[0049] Third stage: Turn off the magnetic field generator, maintain the temperature at 183℃, reduce the pressure to 5.5 MPa, and continue vulcanization for 5.5 min.
[0050] After vulcanization, open the mold, remove the vulcanized rubber sheet, and allow it to cool naturally to room temperature.
[0051] Hot air circulation secondary vulcanization: After the first vulcanization, the rubber sheet is suspended in a hot air circulating aging oven, and the temperature is increased according to the following procedure: The first stage of heating and holding: heating from room temperature (25℃) to 120℃ at a heating rate of 4℃ / min, and then holding at a constant temperature for 30 minutes.
[0052] The second stage of heating and holding: The temperature is increased from 120℃ to 180℃ at a heating rate of 2.5℃ / min, and then held at a constant temperature for 1.5 hours (i.e. 90 minutes).
[0053] Cooling: Turn off the heating power of the oven and allow the rubber sheet to cool naturally to below 60°C in the oven. Remove the rubber sheet to obtain the fatigue-resistant rubber product described in Example 1.
[0054] Example 2
[0055] The difference from Example 1 is that the formulation of the fatigue-resistant rubber is as follows: 100 parts of fluorosilicone raw rubber, 4 parts of anti-fatigue agent, 12 parts of silica, 1.5 parts of modified carbon nanotubes, 12 parts of organomontmorillonite, 4.5 parts of crosslinking agent, 1.2 parts of dispersant, and 5 parts of heat-resistant additive.
[0056] The preparation method is the same as in Example 1.
[0057] Example 3
[0058] The difference from Example 1 is that the formulation of the fatigue-resistant rubber is as follows: 108 parts of fluorosilicone raw rubber, 6 parts of anti-fatigue agent, 18 parts of silica, 0.6 parts of modified carbon nanotubes, 20 parts of organomontmorillonite, 2.0 parts of crosslinking agent, 2.0 parts of dispersant, and 12 parts of heat-resistant additive.
[0059] The preparation method is the same as in Example 1.
[0060] Example 4
[0061] The difference from Example 1 is that the formulation of the fatigue-resistant rubber is as follows: 110 parts of fluorosilicone raw rubber, 2 parts of anti-fatigue agent, 10 parts of silica, 0.5 parts of modified carbon nanotubes, 8 parts of organomontmorillonite, 1.5 parts of crosslinking agent, 0.5 parts of dispersant, and 3 parts of heat-resistant additive.
[0062] The preparation method is the same as in Example 1.
[0063] Example 5
[0064] The difference from Example 1 is that the formulation of the fatigue-resistant rubber is as follows: 102 parts of fluorosilicone raw rubber, 8 parts of anti-fatigue agent, 20 parts of fumed silica, 1.0 part of modified carbon nanotubes, 15 parts of organomontmorillonite, 3.0 parts of crosslinking agent, 3.0 parts of dispersant, and 8 parts of heat-resistant additive.
[0065] The preparation method is the same as in Example 1.
[0066] Example 6
[0067] The difference from Example 1 is that the formulation of the fatigue-resistant rubber is as follows: 106 parts of fluorosilicone raw rubber, 5 parts of anti-fatigue agent, 14 parts of silica, 0.3 parts of modified carbon nanotubes, 16 parts of organomontmorillonite, 2.2 parts of crosslinking agent, 1.6 parts of dispersant, and 7 parts of heat-resistant additive.
[0068] The preparation method is the same as in Example 1.
[0069] Example 7
[0070] The difference from Example 1 is that the formulation of the fatigue-resistant rubber is as follows: 105 parts of fluorosilicone raw rubber, 6 parts of anti-fatigue agent, 16 parts of silica, 1.2 parts of modified carbon nanotubes, 16 parts of organomontmorillonite, 3.5 parts of crosslinking agent, 1.8 parts of dispersant, and 8 parts of heat-resistant additive.
[0071] The preparation method is the same as in Example 1.
[0072] Example 8
[0073] The difference from Example 1 is that the formulation of the fatigue-resistant rubber is as follows: 110 parts of fluorosilicone raw rubber, 7 parts of anti-fatigue agent, 19 parts of silica, 1.3 parts of modified carbon nanotubes, 18 parts of organomontmorillonite, 4.0 parts of crosslinking agent, 2.5 parts of dispersant, and 10 parts of heat-resistant additive.
[0074] The preparation method is the same as in Example 1.
[0075] Comparative Example 1 The difference from Example 1 is that an equal amount of unmodified carbon nanotubes was added, while the other raw materials, proportions and preparation methods were the same as in Example 1.
[0076] Comparative Example 2 The difference from Example 1 is that, in the preparation of organomontmorillonite, only perfluorooctyltrimethylammonium chloride (used alone) was used as the intercalating agent, without the addition of diallyl dimethylammonium chloride. The other raw materials, proportions and preparation methods are the same as in Example 1.
[0077] Comparative Example 3 The difference from Example 1 is that in step S5 of the rubber preparation process, a 2-3T magnetic field is not applied throughout the entire vulcanization process; only the same hot-pressing pressure and time are used. All other raw materials, proportions, and preparation methods are the same as in Example 1.
[0078] Experimental Example Based on the above-mentioned rubber, tests were conducted, and the results are shown in Table 1.
[0079] Test method: Tensile strength, elongation at break, and tensile strength were determined according to GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber"; compression set was determined according to GB / T 7759.1-2015 "Determination of compression set of vulcanized rubber or thermoplastic rubber - Part 1: Under normal and high temperature conditions"; flexural fatigue life was determined according to GB / T13934-2006 "Determination of flexural cracking and crack growth of vulcanized rubber or thermoplastic rubber".
[0080] Table 1
[0081] The embodiments described above are some, but not all, embodiments of the present invention. The detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
Claims
1. A fatigue-resistant rubber, characterized in that, By weight, it includes the following raw materials: 100-110 parts of fluorosilicone raw rubber, 2-8 parts of anti-fatigue agent, 10-20 parts of silica, 0.3-1.5 parts of modified carbon nanotubes, 8-20 parts of organomontmorillonite, 0.5-4.5 parts of crosslinking agent, 0.5-3 parts of dispersant, and 1.5-12 parts of heat-resistant additive.
2. The fatigue-resistant rubber according to claim 1, characterized in that, The method for preparing the modified carbon nanotubes includes the following steps: Carbon nanotubes were added to a hydrogen peroxide solution, ultrasonically dispersed for 20-30 min, refluxed at a constant temperature for 4-5 h, and then separated into solid and liquid components. After washing, hydroxylated carbon nanotubes were obtained. Hydroxylated carbon nanotubes were dispersed in an aqueous ethanol solution, and then perfluorodecyltrimethoxysilane was added to adjust the pH to 4-5. The mixture was stirred for 12-18 hours, centrifuged, washed, and dried to obtain modified carbon nanotubes.
3. The fatigue-resistant rubber according to claim 2, characterized in that, The ratio of carbon nanotubes to hydrogen peroxide is 1 g: (80-100) mL; the amount of perfluorodecyltrimethoxysilane added is 20-40% of the mass of carbon nanotubes.
4. The fatigue-resistant rubber according to claim 1, characterized in that, The preparation method of the organomontmorillonite includes the following steps: Add intercalating agent solvent to sodium montmorillonite suspension and stir at 70-80℃ for 4-6 hours; centrifuge, wash, dry, grind and sieve the reaction solution to obtain organomontmorillonite.
5. The fatigue-resistant rubber according to claim 4, characterized in that, The intercalation solvent is a mixture of perfluorooctyltrimethylammonium chloride and diallyldimethylammonium chloride, with a mass ratio of 3:1 to 4:1; the amount added is 10-15% of the mass of montmorillonite.
6. The fatigue-resistant rubber according to claim 1, characterized in that, The crosslinking agent is 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane; The dispersant is trifluoropropyltrimethoxysilane; The heat-resistant additive is a mixture of cerium oxide and cerium hydroxide in a mass ratio of 1:
1.
7. A method for preparing fatigue-resistant rubber as described in any one of claims 1-6, characterized in that, Includes the following steps: S1, plasticizing raw fluorosilicone rubber to obtain plasticized rubber; S2, put the plasticized rubber into a mixer, then add fatigue-resistant agent, dispersant and heat-resistant additive, and mix for 3-5 minutes; then add fumed silica in batches and mix for 3-5 minutes; then add organomontmorillonite and mix for 3-5 minutes; then add modified carbon nanotubes and mix for 3-5 minutes; discharge the material and sheet it in a two-roll mill to obtain the compounded rubber. S3, add the compounded rubber to the kneader, treat with constant temperature and constant vacuum for 1-1.5 hours, cool, and discharge; S4: Put the rubber compound treated with S3 into a two-roll mill and roll it 3 times. Then add the crosslinking agent and roll it 6-8 times. Then sheet it out and age it at room temperature for 24 hours. S5 undergoes a first vulcanization treatment in a magnetic field, followed by a second vulcanization treatment in a hot air circulating oven, and then natural cooling to obtain fatigue-resistant rubber.
8. The method for preparing fatigue-resistant rubber according to claim 7, characterized in that, In step S5, the primary vulcanization process includes: Vulcanization treatment for 5-7 minutes at 150-160℃, 5-6MPa, and magnetic field strength of 2-3T. Then, vulcanize for 10-12 minutes at 170-175℃, 10-12MPa, and a magnetic field strength of 2-3T. Then, vulcanize at 180-185℃ and 5-6MPa for 5-6 minutes.
9. The method for preparing fatigue-resistant rubber according to claim 7, characterized in that, In step S5, the secondary vulcanization includes: The temperature was increased from room temperature to 120°C at a heating rate of ≤5°C / min, and held at that temperature for 30 min. Heating from 120℃ to 180℃ at a heating rate of ≤3℃ / min, and holding at that temperature for 1-2 hours; Natural cooling.
10. The method for preparing fatigue-resistant rubber according to claim 7, characterized in that, In step S3, the temperature in the kneader is 100-110°C and the vacuum degree is -0.095 to -0.098 MPa.
Citation Information
Patent Citations
High-elasticity fatigue-resistant fluorinated silicone rubber composition and preparation method thereof
CN122080647A
Fatigue-resistant fluororubber with extremely low crack propagation rate as well as preparation method and application of fatigue-resistant fluororubber
CN122302452A